Melacak perkembangan pemikiran keuangan publik Islam - Nafis Irkhami (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2010)
A major source of revenue for an Islamic state since the days of Umar ibn Khatab and until the decay ofthe Islamic civilization was kharaj and ‘ushr. In this paper a fiscal analysis of this levy will be presentedhighlighting what kharaj and ‘ushr understood by Khalifah Umar and early fuqaha. An Islamic govern-ment is not free to handle public money the way it likes. Public money should be spent judiciously toachieve desired goals. It is a duty of the government in a Muslim state not to squander public moneybut to utilize it to improve living standard of people. Technically, this duty needs to be explaining indetail by fuqaha. Encountered of the Islamic public finance thinking as scattered in Islamic literatureindicate that there is no such “missing link” in the construction of economic science as proposed by thethesis of the great gap, especially in the thoughts of public financial.